A ambivalência da ciência em Zygmunt Bauman - Paolo Totaro (Ciências Sociais Unisinos)
This paper intends to emphasize the presence of the phenomenon of ambivalence in the concept of science as presented by Bauman. Therefore, it discusses the role of science in modernization and its failure as a tool designed to overcome ambivalence. The discussion is followed by a final comment that highlights the value of Baumans theses from a predominantly epistemological perspective rather than the sociological perspective notoriously adopted by Bauman himself.